Calculation of the energy levels of excited vibrational states of the HD16O molecule by summing divergent series of the Rayleigh-Schrodinger perturbation theory. The shift of zero-order levels; Optics and Spectroscopy; Vol. 116, iss. 4 - Bykov A. D. Aleksandr Dmitrievich (Spectroscopy Of Atoms And Molecules, 2014)
Title screen